Object Location Memory and Sex Difference: Implications on Static vs. Dynamic Navigation Environments - Uz, Cigdem; Altun, Arif (SEOUL NATL UNIV, INST COGNITIVE SCIENCE, 2014)
In the present study, the effect of a two-type multimedia navigation environment (dynamic vs. static) was investigated on recall performances of learners with different object location memory (OLM) spans (low vs. high). The OLM spans of 34 male and female undergraduate students were determined by a revised location memory test, and the students were separated into high and low groups. In a 2x2 nested ANOVA design, one group studied the static navigation environment, while the other explored the 3-D dynamic environment. While in the 3-D dynamic environment individuals navigated through the smooth display of view changes; in the static environment, 2-D representation of the 3-D real world, objects did not change with the movement of the observer. As participants finished the navigation task, they were given a spatial knowledge recall test. Findings indicated that learners showed higher recall performances in the static environment than the dynamic environment. Gender differences were also observed in terms of recalling spatial knowledge, with males earning the highest scores in the dynamic navigation environment.
Keywords: Object Location Memory; Dynamic environment; Static environment; Sex difference; Navigation; HUNTER-GATHERER THEORY; GENDER-DIFFERENCES; INSTRUCTIONAL-DESIGN; SPATIAL ABILITIES; VIRTUAL ENVIRONMENTS; RECOGNITION MEMORY; FEMALE ADVANTAGE; WORKING-MEMORY; COGNITIVE LOAD; VISUALIZATIONS; Linguistics